Псевдодифференциальная точка поворота в теории сингулярных возмущений - Бобочко, В.Н.; Болилый, В.А. (Нелінійні коливання, 1999)
The asymptotic forms of solutions of singularly perturbed differential equation of the third order with a pseudodifferential turning point is constructed.